2014
DOI: 10.1111/edt.12100
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of revascularization treatment in immature dog's teeth

Abstract: If necrotic-infected canals are effectively disinfected and treated according to the protocol, the ensuing revascularization response is similar to that of vital immature teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 20 publications
4
19
0
1
Order By: Relevance
“…Healing of the periapical lesion in the two experimental groups in this study was similar to the healing rates reported in previous studies (4,18,25,28). Healing of the periapical lesion in the two experimental groups in this study was similar to the healing rates reported in previous studies (4,18,25,28).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Healing of the periapical lesion in the two experimental groups in this study was similar to the healing rates reported in previous studies (4,18,25,28). Healing of the periapical lesion in the two experimental groups in this study was similar to the healing rates reported in previous studies (4,18,25,28).…”
Section: Discussionsupporting
confidence: 90%
“…Endodontic repair procedures are evolving alternatives to the standard treatments for preserving infected immature teeth with open apices (24,25). In a retrospective study, survival rate of teeth after such treatments was reported to be 100% as compared to 77% survival rate of teeth that had undergone apexification with calcium hydroxide (6).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12]14,15,17,21,22 Of these authors, only one provided the requested information, with the remainder either not having the data, or not replying.…”
Section: Resultsmentioning
confidence: 99%
“…[n=NR] Zhu et al 13 [n=5C] Khademi et al 14 [n=8T] Zhang et al 16 [n=13C] Londero et al 17 [n=9C] Saoud et al…”
mentioning
confidence: 99%
“…The dog has been selected as animal model because of its similarities in radicular structure to immature human teeth in their open apex characteristics (3,4,(17)(18)(19)(20) and its high growth rate that allows clinicians to obtain results in shorter experimental periods (21).…”
Section: Discussionmentioning
confidence: 99%